(3OQGSGJ aj GdEOGQI GdYGeI (B/s - (3eLjO, LGSes ((3GdEScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2001)
(3eLGd GdEOGQI GdYGeI(B- (3JWhQ GdEOGQI(B- (3GdEOGQI GdYGeI hGdeONd GdSjGSj(B- (3GdeONd GdfaSj(B- (3GdeONd ef GdfGMjI GdELJeGYjI(B- (3GdacQ GdJfXjej hJWhQg(B- (3CgOGa GdJfXje aj JMbjb GdCgOGa(B- (3GdJfXje GdQSej hZjQ GdQSej(B- (3GdYdGbGJ GdEfSGfjI(B- (3GdCLgRI GdEOGQjI(B- (3efgL GdYed GdEOGQj hCSdhHg(B- (3GdEOGQI haf GdbjGOI(B- (3GJNGP GdbQGQGJ(B.s
Keywords: (3GJNGP GdbQGQGJs; (3GdEOGQI GdYGeIs